2013
DOI: 10.1007/s10900-013-9702-0
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Heart Disease and Its Related Factors in Mongolia: A Nationwide Survey

Abstract: Ischemic heart disease (IHD) remains one of the most important disorders associated with disability and mortality worldwide, and is one of the major causes of cardiovascular diseases in Mongolia. The objective of the current study was to determine the prevalence of IHD and its related factors in a general population in Mongolia. We conducted a nationwide cross-sectional survey between March and September, 2009. General participants were recruited from urban to rural regions in a multistage random cluster sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Overall, 11 papers reported significant findings suggesting that lower SES groups had higher CVD risk, including seven studies from India, [ 52 , 55 - 57 , 62 , 64 , 67 ] two from the Eastern Mediterranean countries of Morocco [ 60 ], and Pakistan [ 69 ], and two from the Western Pacific countries of Mongolia [ 53 ] and Vietnam [ 54 ]. By contrast, four papers reported significant findings suggesting that higher SES groups had worse CVD outcomes, representing findings from three Southeast Asian countries (Bangladesh [ 44 ], Indonesia [ 58 ], India [ 68 ], and Burkina Faso [ 59 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 11 papers reported significant findings suggesting that lower SES groups had higher CVD risk, including seven studies from India, [ 52 , 55 - 57 , 62 , 64 , 67 ] two from the Eastern Mediterranean countries of Morocco [ 60 ], and Pakistan [ 69 ], and two from the Western Pacific countries of Mongolia [ 53 ] and Vietnam [ 54 ]. By contrast, four papers reported significant findings suggesting that higher SES groups had worse CVD outcomes, representing findings from three Southeast Asian countries (Bangladesh [ 44 ], Indonesia [ 58 ], India [ 68 ], and Burkina Faso [ 59 ]).…”
Section: Resultsmentioning
confidence: 99%
“…On average, their body mass index is relatively high. [21][22][23] A previous study among 208 non-gastric cancer dyspeptic non-gastric cancer patients showed approximately 70% were infected with H. pylori. 24 The present study was designed to identify cancer risk factors in Mongolia 25 to assist in developing a screening strategy for individuals at increased risk.…”
Section: Mongolia Is Located In East-central Asia Between Russia Andmentioning
confidence: 99%
“…According to a nationwide survey conducted in accordance with international standards by World Health Organization for non‐communicable disease risk factors, the Mongolian diet contains a high proportion of animal fat and red meat with high salt usage with lower amounts of vegetables and fruit. On average, their body mass index is relatively high . A previous study among 208 non‐gastric cancer dyspeptic non‐gastric cancer patients showed approximately 70% were infected with H. pylori .…”
Section: Introductionmentioning
confidence: 99%
“…11,15,16 These factors may be crucial in the study of metabolic syndrome and correlated risks, 17 but the association between these factors, including SES, and metabolic syndrome remains to be examined in Mongolia. The purpose of the present study was to observe the epidemiologic features of metabolic syndrome (with the IDF criteria) in a general Mongolian population, by using a dataset from a nationwide large-scale population-based cohort study in Mongolia.…”
Section: Introductionmentioning
confidence: 99%